Blood transfusion in obstetrics - Hessah Samar Jaber Almutairi,; Thuria Mabrook S Almabrook,; Alreemi Sonitan H Alotaibi,; Jamila Obeid Almutaira,; Bander Khalad Almutairi,; Ashwag Bander Albakheet,; Noura Bander Albakheet,; Shafa Bander Albakheet,; Rayah Awwad Al. Ahamri,; Faten Falah Al anzi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Severe hemodynamic instability is caused by several pregnancy problems and labor abnormalities, which also act as triggers for additional blood loss throughout pregnancy. In the routine practice of obstetrics, this, with complications from induced or spontaneous abortion & ruptured ectopic pregnancy, manifests as illnesses requiring transfusion. Several prevalent risk factors contribute to the necessity for transfusions of blood and its components throughout labor and pregnancy, including placental complications (abruption, previa, retained placenta, accreta), uterine overdistension (polyhydramnios, multiple gestation), labor augmentation, preterm labor. Preeclampsia, disseminated intravascular coagulation (DIC), and operative delivery—either abdominal or vaginal. Blood transfusions are sometimes criticized as being too late" or "too little in retrospective clinical assessments. Conversely, numerous gynecological illnesses, including uterine or cervical malignancies, fibroid uterus, operations, and dysfunctional hemorrhaging, may result in anemia and necessitate blood & component transfusions in females. Surgical techniques in gynecology require the optimization of hemoglobin before surgery. Components of blood designated for transfusion are generally harvested as anticoagulated total blood (450 milliliters). The majority of donated blood is differentiated into compartments: platelets, packed red blood cells, & fresh frozen plasma (FFP) or cryoprecipitate.